Case Report: A Novel LAMP2 Splice-Altering Mutation Causes Cardiac-Only Danon Disease - Li, Zongzhe; Ma, Fei; Li, Rui; Xiao, Zhichao; Zeng, Hesong; Wang, Dao Wen (Frontiers in Cardiovascular Medicine, 2021)
Danon disease (DD) is a rare glycogen storage lysosomal disorder caused by mutations in the LAMP2 gene. Patients with DD are usually characterized clinically by severe multisystem syndromes. We describe a specific family with a novel pathogenic splice-altering mutation in the LAMP2 gene (c.741+2T>C) with cardiac-only symptoms (frequent ventricular tachycardia, intraventricular block, and hypertrophic cardiomyopathy). Minigene assays were used to evaluate the consequence of the splice-site mutation in the LAMP2 gene. The results showed that the c.741+2T>C mutation led to extra 6-bp preservation of intron 5 at the junction between exons 5 and 6 during transcriptional processing of the mRNA, which creates a stop codon and truncated the LAMP2 protein to 248-amino-acid residues. The mutant LAMP2 protein was predicted to have a conformational change, lacks the important transmembrane domain, and subsequent protein destabilization.